Analysis of Top Design and Floor Design on Tortor Batak Toba Motion - Yusnizar; Sitti Rahmah; Iskandar Muda (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study focuses on Tortor Batak Toba in relation to the social understanding of the supporting community, which is motivated by documentation in the form of writing, video, and other forms that are not recorded and accurate. The research method used is a qualitative descriptive approach and the location of the study in dance study program Sendratasik Department. Data collection methods are carried out with documentation and interviews. The results shows that the structure analysis of Toba Tortor Batak motion form was formed from the top design namely vertical design, horizontal design, pure design, static design, straight design, medium design, and floor design that is straight design, as well as learning design of imitation motion tortor dance.